2020
DOI: 10.1038/s41598-020-58166-5
|View full text |Cite
|
Sign up to set email alerts
|

Topology comparison of Twitter diffusion networks effectively reveals misleading information

Abstract: In recent years, malicious information had an explosive growth in social media, with serious social and political backlashes. Recent important studies, featuring large-scale analyses, have produced deeper knowledge about this phenomenon, showing that disinformation spreads faster, deeper and more broadly than the truth on social media, where bots and echo chambers play an important role in diffusion networks. Following these directions, we explore the possibility of classifying news articles circulating on soc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 34 publications
3
56
0
7
Order By: Relevance
“…Um estudo [Reis et al 2019] argumenta que features relacionadas à fonte da notícias e ao engajamento gerado na sua propagação são as mais discriminatórias na classificação de FN. Uma proposta de classificação de meios de comunicação propagadores de FN baseada na topologia da rede de propagação é apresentada em [Pierri et al 2020]. Propostas de features representando o contexto social incluem perfis difusores de notícias em redes sociais [Shu et al 019a], comportamento social (e.g.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Um estudo [Reis et al 2019] argumenta que features relacionadas à fonte da notícias e ao engajamento gerado na sua propagação são as mais discriminatórias na classificação de FN. Uma proposta de classificação de meios de comunicação propagadores de FN baseada na topologia da rede de propagação é apresentada em [Pierri et al 2020]. Propostas de features representando o contexto social incluem perfis difusores de notícias em redes sociais [Shu et al 019a], comportamento social (e.g.…”
Section: Introductionunclassified
“…Uma nova tendência em processamento de linguagem natural (PLN) é criar modelos através da transferência de aprendizado de representações de linguagens codificadas usando quantidades massivas de dados, tais como BERT (Bidirectional Encoder Representations from Transformers) [Devlin et al 2019]. Outra oportunidade é verificar se a abordagem topológica para verificar veículos de comunicação difusores de FN proposta em [Pierri et al 2020] pode contribuir à classificação de FN independentemente da fonte. O objetivo deste trabalho é experimentar o uso combinado de conteúdo textual da notícia e da topologia das redes de difusão de notícias para a classificação de FN.…”
Section: Introductionunclassified
“…In accordance with current literature [6,[9][10][11]24] we use a "source-based" approach: we do not verify each news article manually but we assign the disinformation label to all items published on websites labeled as such (the same holds for fact-checking articles).…”
Section: Data Collectionmentioning
confidence: 99%
“…Focusing on 2016 US Presidential elections, recent research has shown that false news spread deeper, faster and broader than truth [6], with social bots and echo chambers playing an important role in the diffusion of deceptive information [7,8]. However, it has also been highlighted that disinformation only amounted to a negligible fraction of online news [9][10][11], the majority of which were exposed to and shared by a restricted community of old and conservative leaning people, highly engaged with political news [9][10][11]. In spite of such small volumes, a study suggested that false news (and the alleged interference of Russian trolls) played an important role in the election of Donald Trump [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation